PEMBELAJARAN KALKULUS II BERBASIS TUGAS MELALUI LESSON STUDYSEBAGAI UPAYA UNTUK MENINGKATKAN HASIL BELAJAR MAHASISWA - Suharto, S (Kadikma, 2013)
Abstract.A large classeswith anumber of studentsover 50studentsproved it is not effective inthe implementation oftask-based learning for Calculus II subject in Mathematics Education Department of FKIPJemberUniversity. On the other hand, thattheimplementationof lesson studystarted fromthejointplanning process(plan), implementinglearning(do)as well asevaluation andreflection ofthe results ofthe implementation(see), provides an opportunityto improvestudentlearning outcomes. Thus, the implementation oftask-based learningCalculusII subject throughlesson studyis expected toimprovestudentlearningoutcomes. The study was conductedon learningCalculusII even semester of2011 withthe number of participants of 56students. In this study, studentswere divided intosmall groupsconsisting of5-6 people. The Learning process is donein 4cycles with teacherr teamconsists of 3lecturers. Guidelines fortheearlylearninguseslearning materials developed by Suharto(2007). The resultsshowedthat:1.There is a significant increase inthequalityof learning materilas and varietyof learningscenarios(plan), 2.The role oflecturersis increasinglybetter to facilitate students, providingappropriateassistance,students are able tocomplete thetask ofproblemissuesthroughsmall group discussions, presentinginformationonthe cornerscan then improve the experience, and also to increase students' understandingof thematerial giveneach cycle(do), and 3. studentshave the ability todo self assessment, aware of their mistakes andtheir learning outcomesis improved (see). As acommitmentofprofessionalismlecturer, it is suggested thatlesson studycan be applied toall learning process. Key Words :Task Based, Studying in a Group, Quality and Students Outcomes